Mononucleosis: A Possible Cause of Idiopathic Hypersomnia - Sforza, Emilia; Hupin, David; Roche, Frédéric (Frontiers in Neurology, 2018)
Idiopathic hypersomnia is a rare central hypersomnia of unknown physiopathology. In this study, we determine if the presence of mononucleosis evaluated by serological markers of Epstein Barr virus infection plays a role in this hypersomnia. Ten patients with a suspicion of Idiopathic hypersomnia (IH) underwent to clinical assessment, 24h polysomnography and serologic testing for mononucleosis including Viral Capside Antigen (VCA) IgG, the VCA IgM and the EBV nuclear antigen (EBNA) were measured. None of the patients reported neurological inflammatory disease and viral infection prior the onset of the disease. Compared to the laboratory serological reference values, all patients had high levels of VCA IgG and EBNA with lower level of VCA IgM, overall indicating past infection. This study shows that prior mononucleosis may predispose some subjects to idiopathic hypersomnia suggesting the role of inflammatory and immunological processes in this sleep disorder.